How to draw fantasy art and RPG maps : step-by step cartography for gamers and fans - Blando, Jared (Cincinnati, Ohio : Impact, 2015)
"Orcs prepare for battle against high Elves, Dwarves retreat to the mountains and men march to the sea to reclaim crumbling fortresses. Fortunes are decided. Kingdoms are lost. Entire worlds are created. This book will teach you to bring your fictional realm to life with simple step-by-step instructions on how to draw authentic fantasy maps. Set the stage for adventure by illustrating domains, castles and battle lines, mountains, forests and sea monsters! Learn to create completely unique and fully functional RPG maps time and time again on which your world can unfold.
Visit impact-books.com/fantasymaps for free bonus content.
Keywords: Fantasy in art -- Technique; Fantasy games; Maps; Map drawing; Cartography